Single Visit Endodontics: Efficient Practice or Just a Time-Saving Strategy? - babu, Athul; Goel, Shrutika; Rebello, Pawan; Sharma, Himanshu; Prakash, Pallavi; Sekhar Das, Sitansu (Journal of Neonatal Surgery, 2025)
Single-visit endodontics is increasingly recognized for its potential to streamline dental treatment by completing root canal therapy in a single appointment. This study evaluates the clinical efficacy, patient satisfaction, and post-treatment complications associated with single-visit endodontics, comparing it to the traditional multi-visit approach. Simulated data from 25 patients were analyzed, with 15 undergoing single-visit treatment and 10 undergoing multi-visit treatment. Key findings indicate comparable clinical success rates between the two approaches, with single-visit endodontics achieving higher patient satisfaction due to reduced chair time and convenience. However, a slight increase in mild post-treatment complications was observed in single-visit cases. These results suggest that single-visit endodontics is an effective and patient-centric practice, provided that case selection is done carefully to minimize complications.